2018
DOI: 10.1016/j.applthermaleng.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of a meso-scale combustor with electrospray technique using liquid ethanol as fuel

Abstract: A new meso-scale combustor to be coupled with energy conversion modules was fabricated. The volume of the combustor was on the order of a few cubic centimeters. Ethanol was applied as fuel and electrosprayed at the flow rate of 3.5ml/h. Stable flame which shaped in a rounded slice was achieved near the mesh as equivalence ratios varying from 0.9~1.7 without external heating and catalyst. The temperatures of flame, combustor outer wall and exhausted gas were measured. Flame temperatures were within the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The combustion efficiency was improved by 4.5% for combustor B, indicating the catalyst's significant role in enhancing the combustor's performance. Gan et al [52] developed a mesoscale electrospray combustor working on ethanol coupled with an energy conversion module. The combustor was found to sustain stable flames within a range of equivalence ratios from 0.9 to 1.7.…”
Section: Combustionmentioning
confidence: 99%
“…The combustion efficiency was improved by 4.5% for combustor B, indicating the catalyst's significant role in enhancing the combustor's performance. Gan et al [52] developed a mesoscale electrospray combustor working on ethanol coupled with an energy conversion module. The combustor was found to sustain stable flames within a range of equivalence ratios from 0.9 to 1.7.…”
Section: Combustionmentioning
confidence: 99%
“…Their obtained results can be suitable for developing combustion-based power generation systems. Gan et al [12] developed a meso-scale combustor taking advantage of an electrospray technique. The thermal efficiency of the combustor ranged from 22.0% to 48.8%, which can be used to couple with energy conversion modules.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion of porous media [10,11], combustion of bluffbody [12-14], method of external heating [15], besides the field being electrical [16]. As a consequence, the associated study findings revealed that these techniques significantly increase the limit of blow-off [17,18], thermal function [19,20], and emissions combustion [21,22]. However, a typical micro TPV system is shown in Figure 1 involves 3 prime components: An emitter, a fuel source, and a TPV cell array.…”
Section: Introductionmentioning
confidence: 99%